Thai health care provider knowledge of neonatal male circumcision in reducing transmission of HIV and other STIs - Kriengkrai Srithanaviboonchai (2018)
Â© 2015 Srithanaviboonchai et al. Background: Male circumcision (MC) reduces the risk of female-to-male transmission of HIV and other sexually transmitted infections (STIs). MC has not been practiced as a disease prevention measure in Thailand probably because of low recognition of its benefits among stakeholders. Neonatal male circumcision (NMC) is simpler, safer and cheaper than adult MC. This study aimed to assess Thai health care provider knowledge of benefits implementing NMC in Thailand. Methods: Multi-stage sampling identified 16 government hospitals to represent various hospital sizes and regions of the country. Researchers administered a fixed choice questionnaire, developed by the research team based on a previous study, to physician administrators, practicing physicians, and nurses whose jobs involved NMC clinical procedures or oversight. The participants reviewed printed educational materials on the benefits of NMC during questionnaire completion. Data were analyzed using descriptive statistics, chi square tests, odds ratios, and logistic regression. Results: One hundred thirty-three individuals participated in this quantitative study. Only 38 % of the participants agreed that NMC reduced the risk of sexual transmission of HIV while 65 % indicated that they knew that NMC prevented STIs. Most participants recognized the benefits of NMC on hygiene (96 %) as well as cancer prevention (74 %). Major concerns raised were potential trauma to the child, child rights and safety of NMC. After reviewing written information about the benefits of NMC, 59 % of the participants agreed that NMC should be offered in their hospital. Physicians and nurses who had previous experience with circumcising patients of all ages were more reluctant to have NMC performed in their hospital. Conclusions: A clear policy advocating NMC, thorough preparation of health facilities, and staff training are needed before NMC could be used in Thailand as prevention strategy for HIV and other STIs.